Physicochemical, biological and drug-release properties of gallium crosslinked alginate/nanoparticulate bioactive glass composite films - Mouriño, Viviana Silvia Lourdes (2011)
The aim of this work was to develop biodegradable and bioactive materials with sufficient structural integrity and prophylaxis effect against infection based on alginate-bioactive glass composite. The incorporation of bioactive glass nanoparticles (NBG) into Ga-crosslinked alginate films significantly improved their mechanical properties when compared with films fabricated with micron-sized bioactive glass particles. In addition, Ga-alginate films containing NBG induced a bacteriostatic effect in vitro towards S. aureus due to the presence of Ga ions (Ga3+), whose release is controlled solely by crosslinking the ion with alginate. Biomineralization studies in simulated body fluid suggested the deposition of hydroxyapatite on the surface of the films indicating their bioactive nature. In addition, the films were shown to feature biocompatibility toward osteoblast-like cells. Thus, it was shown that Ga-crosslinked composite films possessed relevant physicochemical, biological and controlled bacteriostatic effects which make these materials promising candidates for bone tissue engineering applications.